The Interplay of Human and Social Capital in Entrepreneurship in Developing Countries: The Case of Uganda - Rooks, Gerrit; Szirmai, Adam; Sserwanga, Arthur (United Nations Universitty, 2009)
This paper discusses the characteristics and determinants of entrepreneurial behaviour in Uganda. It is based on a recent survey of urban and rural entrepreneurs, executed in May 2008. The main dependent variables are business success, gestation activities and innovative performance. The paper focuses in particular on the interplay of human and social capital in determining entrepreneurial performance. A prominent question in the literature is whether human capital and social capital act as complements or substitutes in furthering entrepreneurial dynamism. We find that Ugandan enterprises are predominantly very small and not very dynamic. Most enterprises are young, with little or no growth of employment since start-up. Only a very small subset of sample entrepreneurs could be classified as entrepreneur in the dynamic Schumpeterian sense.
Keywords: Social capital; Human capital; Entrepreneurship; Developing countries